2007
DOI: 10.1016/j.neurobiolaging.2006.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular volume and dementia progression in the Cardiovascular Health Study

Abstract: Elevated cerebral ventricular volume may be associated with dementia risk and progression. A fullyautomated technique that agreed highly with radiological readings was used to estimate lateral ventricle volume on MR scans done at baseline in 1997-99 of 377 subjects in the Cardiovascular Health Study (CHS) from the Pittsburgh Center. 327 subjects were normal or diagnosed with mild cognitive impairment (MCI) at baseline and were evaluated 4 years later. Baseline ventricular volume was analyzed in multivariate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 48 publications
9
81
1
1
Order By: Relevance
“…If automated ventricular segmentation methods become as reliable as manual tracing, these shape analysis methods may be efficiently extended to larger samples. We are currently validating more automated approaches for creating these surface maps (Carmichael et al, 2007). In this study, a 9-parameter global scaling transform was applied to each individual brain, to match the standardized average brain template.…”
Section: Discussionmentioning
confidence: 99%
“…If automated ventricular segmentation methods become as reliable as manual tracing, these shape analysis methods may be efficiently extended to larger samples. We are currently validating more automated approaches for creating these surface maps (Carmichael et al, 2007). In this study, a 9-parameter global scaling transform was applied to each individual brain, to match the standardized average brain template.…”
Section: Discussionmentioning
confidence: 99%
“…61 Studies are currently under way to define ventricular changes in subjects with MCI and AD. A similar approach was used by Carmichael et al, 42 who reported that among normal subjects larger ventricles at baseline were predictive of future progression to dementia.…”
Section: Fig 5 This Longitudinal 3d Mri Studymentioning
confidence: 99%
“…41 Ventricular enlargement appears to have a higher predictive value in the earlier transition stages as opposed to the later stagethat is, from normal cognition to MCI or AD and less so from MCI to AD. 13,42 VBM has also been used to reveal the spatial profile of aging and gender effects in normal subjects, 28,43,44 frontotemporal and Lewy body dementia, [45][46][47][48] Parkinson's disease, and even herpes simplex encephalitis. 49 For analysis of cortical gray matter atrophy, VBM may not be optimal.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations